Pedagogia do surdo: formação continuada para surdos instrutores e professores da Língua Brasileira de Sinais - Libras - Oliveira, Priscilla Roberta Gaspar de (2019)
This dissertation, entitled Deaf Pedagogy: continuing education for Deaf Instructors and Teachers of the Brazilian Sign Language – “Libras”, which focuses on an alternative research for the constitution of Libras, in full, as a curricular area, has as a general objective to identify the methodology and the didactics adopted by Deaf instructors and teachers in teaching Libras as first and second language. This study, here it involves two parts: the first part is the experience lived by the author since she, herself, is deaf and a member of the deaf community, where the deaf sign language and culture flow, leading to the identity formation of the deaf; the second part as a Deaf and Listening teacher, aiming at understanding the formation of deaf instructors and teachers. Founded on theoretical basis authors were involved in Deaf Education, such as: Skliar, Campello, Reis, Quadros and others, and have proved how Deaf professionals are seen before the school curriculum; There is no record in practice about how to interfere in a change concerning their academic development and how to collaborate in methodological and didactic innovation in teaching Libras as first and second language. As a research methodology, deaf instructors are the main subject of this dissertation in order to guarantee a real mapping of conceptions, formation and meanings of teaching. Therefore, as a result in construction, this work has the purpose to point out possibilities and paths for the construction of a curriculum that can create new views from the others involved in the Education of the Deaf, making them realize the importance of the work developed in the teaching of Libras, as first and second language